Impaction of Permanent Canine due to Retaining of Deciduous Teeth - Nessa, Jebu; Akter, Mahmuda; Hasan, Md. Kamrul (Medicine Today, 2012)
Medicine Today 2009 Volume 21 Number 02 Page 82-83 DOI: http://dx.doi.org/10.3329/medtoday.v21i2.12554